Informal carer in Portugal: moving towards political recognition in Portugal. (13th November 2019) - Fronteira, I; Simoes, J; Augusto, G
Abstract: : Informal care represents around 80% of all long term care provided in EU countries. Nevertheless, the needs for this type of care are expected to increase in the coming years in all OECD countries. Portugal is among the OECD countries with the highest ageing index (21.5% of the population was older than 65 years in 2017) due to high life expectancy and low fertility rates. As this demographic trend establishes, Portugal is expected to have more than 40% of the population over 65 years in 2037, and the expected prevalence of dementia is 3%, in 2050. In 2015 there were 2.1% of people over 65 receiving long-term care, representing 52% of all long-term care users. Around 38% were receiving care at home. It is estimated that 287, 000 people in Portugal depend on informal carers. The agenda towards the official recognition of informal cares has been push forward in the country. Since 2015, several recommendations have been issued by the Parliament as well as legislative initiatives and a proposal for a Status of the Informal Carer is currently under discussion. We analyse the process of formulation of this policy in terms of sectors and stakeholders involved, definition and scope of informal carer, rights and obligations, role of the person being cared for, formal protection (e.g., labor, social, financial, training) and implementation. Recognition of the informal carer is a sector wide approach. One of the main features is the economic, social and labor protection mainly through reconciliation between work life and caring activities and promotion of the carer's well being. Notwithstanding, and from a health system perspective, community health teams are to be the focal point for informal carers, supporting and providing specific training whenever needed. Despite its relevance, informal care should not be professionalized and responsibility of care should not be shifted from health services to informal carers. Key messages: Needs for informal care are expected to increase in the coming years in OECD countries. Recognition of the informal carer is a sector wide approach.